2007
DOI: 10.1037/1528-3542.7.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Garner interference reveals dependencies between emotional expression and gaze in face perception.

Abstract: The relationship between facial expression and gaze processing was investigated with the Garner selective attention paradigm. In Experiment 1, participants performed expression judgments without interference from gaze, but expression interfered with gaze judgments. Experiment 2 replicated these results across different emotions. In both experiments, expression judgments occurred faster than gaze judgments, suggesting that expression was processed before gaze could interfere. In Experiments 3 and 4, the difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
73
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 68 publications
(181 reference statements)
15
73
4
Order By: Relevance
“…Bindemann et al (2008) showed that emotion categorization varied as a function of the number of facial expressions included in a given paradigm and suggested that the results of Adams and Kleck likely reflected strategic task effects rather than real effects of gaze on facial expression categorization (Bindemann et al, 2008). Graham and LaBar (2007) also showed that gaze direction modulates expression processing only when facial expressions are difficult to discriminate (i.e. more ambiguous).…”
Section: Gaze Direction In Face Perception Gender Discrimination Idmentioning
confidence: 98%
See 1 more Smart Citation
“…Bindemann et al (2008) showed that emotion categorization varied as a function of the number of facial expressions included in a given paradigm and suggested that the results of Adams and Kleck likely reflected strategic task effects rather than real effects of gaze on facial expression categorization (Bindemann et al, 2008). Graham and LaBar (2007) also showed that gaze direction modulates expression processing only when facial expressions are difficult to discriminate (i.e. more ambiguous).…”
Section: Gaze Direction In Face Perception Gender Discrimination Idmentioning
confidence: 98%
“…However, other studies failed to reproduce the original results of Adams and Kleck (Bindemann et al, 2008;Graham and LaBar, 2007). Bindemann et al (2008) showed that emotion categorization varied as a function of the number of facial expressions included in a given paradigm and suggested that the results of Adams and Kleck likely reflected strategic task effects rather than real effects of gaze on facial expression categorization (Bindemann et al, 2008).…”
Section: Gaze Direction In Face Perception Gender Discrimination Idmentioning
confidence: 98%
“…Studies that manipulate the discriminability of gaze and expression report an overall processing speed advantage for judgements of gaze direction. However when discriminability of gaze is made more difficult, emotion expression is processed and gaze and emotion interactions are observed 36 . This suggests that in patients, top-down control compromised perceptual processing of gaze cues, and led to gaze and emotion expression interactions, reflecting possible underlying deficits in selective attention 37 .…”
Section: As Taskmentioning
confidence: 99%
“…Eye gaze can provide a number of different cues for social interactions and emotional perception. Adams and Kleck [62] proposed that gaze direction is associated with approach-avoidance behavioral tendencies in that they found that approach-oriented emotions (anger and joy) were processed more quickly with direct gaze, while avoidance-oriented emotions (fear and sadness) were processed more quickly with averted gaze. Graham and LaBar [62] found that gaze direction interfered with expression processing only when facial expression was difficult to discriminate by using Garner paradigm, and they suggest that the processing of eye gaze and facial expressions are only partially dependent.…”
Section: Figurementioning
confidence: 99%